Seventeenth-Century Pamphlets as Constituents of a Public Communications Space: A Historical Critique of Public Sphere Theory. (January 2019) - Verhoest, Pascal
A public sphere in which people can freely discuss worldly affairs is arguably an essential building block of deliberative democracies. As a theoretical and historical concept, however, the public sphere concept is far from unequivocal. This article reviews Habermasian public sphere theory and particularly his failure, according to critics, to establish the 'bourgeois public sphere' as an historical category. It provides a more realistic historical account that helps to reframe contemporary conceptions of the public sphere. It argues that the 17th century's culture of pamphleteering created the space for a proto-public sphere, characterized as a complex network of discursive practices mixing commercial doggerel, state-sponsored propaganda and reasoned argument. These practices were part of contradictory but mutually constitutive processes in the context of religious and political struggles that coincided with the gestation of parliamentary democracy.